BETWEEN INNOVATION AND UNCERTAINTY: A COMPREHENSIVE ANALYSIS OF THE RISKS ASSOCIATED WITH OX513A AND OX5034 GENETICALLY MODIFIED MOSQUITOES IN ARBOVIRUS CONTROL - Castro, Leonardo Gonçalves Guimarães de; Vital, Anne Josiele de Lima; Nunes, Isadora Sofia Souza; Oliveira, Kathylin Glenda Marques; Couto, Luana Cristina da Silva; Barros, Bárbara Avelar Ferreira (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
The risks associated with genetically modified mosquitoes (GMOs) in combating arboviruses, specifically the strains of Aedes aegypti developed by Oxitec, have raised growing concerns due to potential dangers. With dengue becoming endemic in over 100 countries, the search for alternatives in vector control includes the use of GMOs. However, the introduction of these mosquitoes raises considerable concerns regarding potential risks to ecosystems and human health. Employing PRISMA guidelines, a database search identified 913 studies, of which only 4 were included after careful selection. The results highlight relevant findings, such as genomic instability in strains like OX513A and performance disparities between genetically modified mosquitoes and their wild counterparts. The review emphasizes the critical importance of dengue control in Brazil, considering factors like virus genetic variability and challenges in implementing control strategies, including the use of GMOs. Regulation of these organisms is conducted by CTNBio; however, the lack of consensus among various agencies raises doubts about the benefits of implementing these organisms. Given this landscape, the review underscores the ongoing need for monitoring the risks associated with genetically modified mosquitoes, encompassing not only biological implications but also environmental consequences. This approach is imperative for a comprehensive and informed assessment of the efficacy and safety of these organisms in the context of arbovirus control.